RELATIONSHIP OF SECRETED PHOSPHOPROTEIN 1 PROMOTER /EXON 3 GENE POLYMORPHISM/ G>A/1207 & A>G /1212 IN SOME ECONOIC VALUES AND LIVER ENZYME OF AWASSI SHEEP - Al-Huboby, H. A.; Al-Anbari, N. N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to identify the genetic polymorphism of the Secreted phosphoprotein 1 (SPP1) gene in a sample of Awassi sheep consisting of 48 ewes and its 62 newborns. This study lasted for six months, The results revealed that there were two variations (2 SNPs) in the Promoter Exon 3 of gene SPP1, the first variance SNP1 the position was (SNP1 A > G: P/1212/(84 bp), AG. The second variance Snp2, G > A: P/1207/ (92 bp), There were two genetic components of this gene, GG and GA, at a percentage rate of 60.42 and 39.58%, respectively, and there were high-morale (P≤0.01) differences in the birth weight of the ewe, The GA hybrid ewe outperformed the G-pure terrestrial genetic structure. This study concludes that the mutant GG genetic structure does not appear in the SNP1 and AA does not appear in the SNP2 of the gene’s studied region. There is a correlation between the heterogeneity obtained from the study of SPP1 gene and the production of daily milk and some liver enzymes in passive sheep that can be exploited in election and improvement programmes.